The impact of historical event on the memory of public place - Zamwa Radha Mohammed; Raz Saeed Faraj (Sulaimani Journal for Engineering Sciences)
This paper aims to clarify a subject related to historical events' tangible and intangible effects on public space and how we comprehend the other side of the non-physical component. This research compares a particular example of the public forum of the Jewish holocaust memorial with Sulaymaniya City and Halabja City, Jewish holocaust memorial has an exceptional character with a specific local spirit as it results from dramatic historical occurrences. Preserving this public area and its value is indispensable to show this unfortunate event by which the Jewish holocaust memorial was shaped. Every public space keeps its identity and a specific meaning which is impacted by historical events concerning the place and time. It so is comprehending what is intended to show transparently. Unlike regular public plazas and places, influenced public place has own message to convey, which can tell the story of any event that had happened at that time. However, interpreting hidden occurrences can be shown throughout an ancient public space, allowing further generations to understand what happened before them. Consequently, not only will the historical event be considered a cultural value that clarifies its identification, but the local community also confer a particular meaning to a building since the building or the place may have a meaning to them. Nevertheless, the lack of sense of the soul in a particular place shows that this public place could not fulfil to convey or interpret the historical background (event) to the individuals in order to be more interacted with and preserved by the society who has a significant influence on conserving those building which has comprehensive meaningful. In order to understand why a historical event would leave its fingerprint on a specific place, clarifying the tangible and intangible components of the event is imperative to understand the social and cultural value allocated by the mentioned event. Eventually, tangible and intangible factors of a historic event acquire a public space with determined interpretation or comprehension, by which a significant integration between people and the public will likely be established.